Perspectives on Everyday Life Challenges of Danish Young People With Duchenne Muscular Dystrophy (DMD) on Corticosteroids - Charlotte Handberg; Ulla Werlauff; Ann-Lisbeth Højberg (SAGE Publishing, 2022)
This study aimed to investigate perspectives on everyday life challenges of young persons with Duchenne muscular dystrophy in Denmark treated with corticosteroids perceived by young persons and their parents to improve rehabilitation interventions. Nineteen semi-structured interviews were conducted: 10 individual interviews with 10 persons with DMD and six individual interviews with parents (five mothers and one father) and three couple interviews (three mothers and three fathers). The analysis was guided by interpretive description methodology and Antonovsky's Sense of Coherence theory. The results indicated that persons with Duchenne muscular dystrophy existed in a flux between experiencing greater Sense of Coherence revolving around normality and less Sense of Coherence exposing their vulnerability which unfolded in four opposing themes: (1) bodily ability and disability, (2) content and anxious, (3) sociable and lonely, and (4) independent and dependent. Future rehabilitation should aim at supporting resistance resources promoting bodily ability, being content, sociable, and independent.